Examining the presence of sarcopenia in women with rheumatoid arthritis: Case-control study - Akar Begum; Calik Bilge Basakci; Kabul Elif Gur; Akbaş Ayşe Nur Bayindir; Cobankara Veli (Sciendo, 2024)
The aim of this study was to compare the frequency of sarcopenia, functional status, fear-avoidance behaviors, biopsychosocial status and quality of life in RA women with healthy controls.